Empowerment in Seven Selected American Songs: The Ideational and Interpersonal Meaning Title - Rohmah, Desi Lailatul; Silalahi, Pininta Veronika (CV. Era Digital Nusantara, 2023)
The recent study aims to analyse the ideational and interpersonal meaning in seven selected empowerment songs’ lyrics. The objectives of the study are to describe the characteristics and types of interpersonal meaning: mood and modality; and the types of transitivity processes. The research design applied in this study is descriptive qualitative. The data is the lyrics of seven selected songs: Brave by Sara Barelies; Fireworks, and Roar by Katy Perry; Who Says by Selena Gomez; Love Myself by Hailee Steinfeld; Fight Song by Rachel Platten; and I love Me by Demi Lovato. The finding shows the dominant mood of all the lyrics is declarative mood; and the modality are: “can” in song 1; “wouldn’t” and “would” in song 2; “don’t have to”, “cannot”, and “could” in song 3; “can’t” in song 5; “can”, “might”, and “will” in song 6; “can’t” and “should” in song 7. Further, the analysis showed that all the transitivity process found in the lyrics include: material, mental, relational, behavioural, verbal, and existential.